“To be an Asian Girl”: Examining Identity Construction and School Punishment through Found Poetry - Sanchez, Shena; Gu, Sun Young (Art/Research International)

(untitled) (University of Alberta, 2024)
In this study, we explore how three Asian high school girls from poor/working-class families construct their identity in relation to their experiences with school punishment and anti-Asian sexism rooted in model minority and perpetual foreigner stereotypes. Using found poetry as a method, along with intersectionality and Asian feminist frameworks, we analyze sister circle and kitchen table focus group interviews and diagramming data. We find that, despite their different ethnicities and geographic locations, participants shared significant experiences and perspectives that centered their resistance to anti-Asian sexism, agency and personhood, and familial responsibilities as a source of motivation to excel academically.